Remaja dan kegelisahan akan masa depan dalam perspektif eksistensialisme - Sativa, Oryza; Ilmmamufidah, Nurul (Maliki Interdisciplinary Journal, 2026)
In the context of social developments in today's modern era, one issue that is increasingly relevant is the number of teenagers who experience anxiety about the future in line with social demands and the transition process towards adulthood. In this phase they are faced with choices regarding education, work and forming their identity. This is the root of anxiety in individuals, this anxiety not only arises as a result of social and psychological pressure, but also from freedom and a sense of responsibility for all choices that will have an impact on the future. From an existentialist perspective, anxiety is considered as part of self-maturation so it is not only seen as an obstacle to self-development, but also as an opportunity for self-reflection in searching for the meaning of life and determining future choices. The aim of this article is to look at the causes of anxiety not only from psychological science but also from the philosophy of existentialism, which is also expected to provide a deeper understanding of the phenomenon of teenage anxiety as well as knowing the various types of existential anxiety and analyzing them from an existentialist perspective.